Near-death experiences, posttraumatic growth, and life satisfaction among burn survivors. (16th March 2017) - Royse, David; Badger, Karen
ABSTRACT: Survivors of large burns may face positive and negative psychological after-effects from close-to-death injuries. This study is the first to examine their near-death experiences (NDEs) and posttraumatic growth (PTG) and life satisfaction afterwards. With an available sample of 92 burn survivors, half met the criteria for an NDE using an objective scale. Those who indicated religion was a source of strength and comfort had high scores on life satisfaction, PTG, and the NDE Scale. Individuals with larger burns reported greater PTG than those with smaller total body surface area burned (TBSA). There were no significant differences on life satisfaction, PTG, or NDEs when examined by gender or years since the burn injury. Elements of the NDE most frequently reported were: An altered sense of time, a sense of being out of the physical body, a feeling of peace, vivid sensations, and sense of being in an "other worldly" environment. Social workers and other health providers need to be comfortable helping burn survivors discuss any NDEs and process these through survivors' spirituality and religious belief systems as they recover.